2004
DOI: 10.1139/x04-136
|View full text |Cite
|
Sign up to set email alerts
|

Estimated realized gains for first-generation slash pine (Pinus elliottii var. elliottii) tree improvement in the southeastern United States

Abstract: Realized gains from selection of the first-generation breeding population of slash pine (Pinus elliottii Engelm. var. elliottii) were estimated using data from 38 field trials planted in large rectangular plots in the southeastern United States. The trials consisted of material selected for volume growth and planted by the Cooperative Forest Genetics Research Program at the University of Florida (19 trials) and by the Plantation Management Research Cooperative at the University of Georgia (19 trials). All tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…The single-tree-plot design of the plantation might have also affected genetic parameters of the traits, as the measurements from such plots are influenced by competition among different genotypes [27]. However, low planting density likely had postponed the onset of inter-tree competition, therefore reducing exaggeration of the genotypic variance of growth traits [5,16,28].…”
Section: Discussionmentioning
confidence: 99%
“…The single-tree-plot design of the plantation might have also affected genetic parameters of the traits, as the measurements from such plots are influenced by competition among different genotypes [27]. However, low planting density likely had postponed the onset of inter-tree competition, therefore reducing exaggeration of the genotypic variance of growth traits [5,16,28].…”
Section: Discussionmentioning
confidence: 99%
“…Short-term evaluation of seedling families for rust resistance is a key step in developing resistance. Although field progeny tests are often used without artificial inoculation trials for FR breeding southern pines [24][25][26], a combination of field and artificial inoculation tests are routinely used for WPBR. The use of small seedlings allows for the efficient testing of progeny of hundreds or even thousands of parent trees in a relatively short time period.…”
Section: Resistance Testingmentioning
confidence: 99%
“…Barber [27] demonstrated wide variation in susceptibility from open-pollinated progeny of slash pine and it was observed that resistance was high in hybrids between shortleaf and slash and shortleaf and loblolly pines [28]; most selection for resistance has continued to focus on loblolly pine [24][25][26]. Surviving trees from high-hazard sites were clonally propagated by grafting, planted in seed orchards, and breeding for rust resistance had begun.…”
Section: Resistance Testingmentioning
confidence: 99%
“…However, these can produce biased estimates of growth traits that are affected by competition, favoring entries with initially fast growth, while entries which are initially slow-growing are disfavored (Cannel 1982;Foster 1992;Vergara et al 2004;Ye at al. 2010).…”
Section: Discussionmentioning
confidence: 99%